2019
DOI: 10.2478/prilozi-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between HPV DNA Testing and HPV E6/E7 MRNA Testing in Women with Squamous Cell Abnormalities of the Uterine Cervix

Abstract: Introduction: The aim of the study was to compare the results of two human papillomavirus (HPV) diagnostic techniques: human papillomavirus deoxyribonucleic acid (HPV DNA) testing and human papillomavirus E6/E7 messenger ribonucleic acid (HPV E6/E7 mRNA) testing in women with squamous cell abnormalities of the uterine cervix. Material and Methods: Comparative prospective study, conducted in the period from January 2016 to June 2017 of 128 sexually active women, age groups of 20 to 59 years (40.50 ± 10.85) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…In this study, the positive rate of HPV DNA assay was 85.3%, which was much higher than that of the HPV E6/E7 mRNA test (61.6%).This relatively high percentage of HPV DNA infection in cases with positive cervical cytology is consistent with some previously published studies [22,23,27].There was an association between E6/E7 mRNA expression and histology (OR = 106.12) [28]. Data analysis from our study showed an association between the results of HPV E6/E7 mRNA, histological diagnosis, and the TCT grade.The positive rate of HPV E6/E7 mRNA and histological diagnosis increased with the upgrade of TCT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the positive rate of HPV DNA assay was 85.3%, which was much higher than that of the HPV E6/E7 mRNA test (61.6%).This relatively high percentage of HPV DNA infection in cases with positive cervical cytology is consistent with some previously published studies [22,23,27].There was an association between E6/E7 mRNA expression and histology (OR = 106.12) [28]. Data analysis from our study showed an association between the results of HPV E6/E7 mRNA, histological diagnosis, and the TCT grade.The positive rate of HPV E6/E7 mRNA and histological diagnosis increased with the upgrade of TCT.…”
Section: Discussionsupporting
confidence: 91%
“…The performances of the HPV DNA assay and HPV E6/E7 mRNA test were analyzed in young women.HPV DNA was similar to HPV E6/E7 mRNA in sensitivity,PPV, and NPV,while there was no signi cant difference between the two methods.Still, the speci city of HPV E6/E7 mRNA(47.3%)was signi cantly higher than that of HPV DNA(16.0%) (P<0.01).In the study of Munkhdelgeret al that included 188 women with the squamous intraepithelial cervical lesion, HPV E6/E7mRNA testing was more speci c than HPV DNA assay (85.00% versus 40.83%) [29].In their study,DrageDabeski et al [27]screened a group of 128 sexually active women aged 20 to 59 years with squamous cell abnormalities on the cervical cytology, reporting a greater speci city (88.89%)and greater positive predictive value (93.59%)of HPV E6/E7 mRNA test.The speci city of the HPV E6/E7 mRNA test in our study was signi cantly lower than in the above studies, probably because of the differences in age and number of cases.…”
Section: Discussionmentioning
confidence: 89%
“…Previous literature also showed that HPV E6/E7 mRNA testing has higher specificity and positive predictive than HPV DNA testing. 22 27 In our study, out of the total patients who had normal biopsy findings (38), five had HPV DNA positive and none of them had the expression of HPV E6/E7 mRNA showing that E6/E7 mRNA expression is more specific for cervical carcinogenesis as compared with the presence of only HPV DNA. Yao et al also concluded in their study that the HPV E6/E7 mRNA test were highly concordant with cytology test results, and both the diagnostic modalities resulted in similar sensitivity, specificity, PPV, and NPV while identifying HSIL+ lesions.…”
Section: Discussionmentioning
confidence: 53%
“…Origoni et al, 19 Ho et al, 20 and Molden et al 21 demonstrated the positivity of HPV E6/E7 mRNA among women with abnormal cytology as 26, 21, and 22.8%, respectively. However, in a recent study by Dabeski et al 22 high-risk HPV E6/E7 mRNA infection was detected in 60.94% of patients with squamous cell abnormalities of the cervix. These differences could be due to different sample sizes in different studies along with different methodologies used.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies have compared the performance of E6/E7 mRNA-based assays with hrHPV DNA testing, and they all concluded that E6/E7 mRNA testing had higher specificity and PPV for HSIL and invasive squamous cell carcinoma (ISCC), compared to hrHPV DNA testing [78][79][80][81]. Furthermore, Fontecha et al claim that the mRNA test combined with cytology has more clinical relevance than hrHPV DNA screening in women with low-grade lesions [75].…”
Section: Hrhpv Transcriptional Statusmentioning
confidence: 99%